2003
DOI: 10.1002/polb.10658
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐level alignment at metal–organic and organic–organic interfaces

Abstract: This article reports on the electronic structure at interfaces found in organic semiconductor devices. The studied organic materials are C60 and poly (para‐phenylenevinylene) (PPV)‐like oligomers, and the metals are polycrystalline Au and Ag. To measure the energy levels at these interfaces, ultraviolet photoelectron spectroscopy has been used. It is shown how the energy levels at interfaces deviate from the bulk. Furthermore, it is demonstrated that the vacuum levels do not align at the studied interfaces. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 36 publications
2
25
0
2
Order By: Relevance
“…Note that the same alignment of the C 60 energy levels has been observed at its interfaces with oligomer homologues of poly(para-phenylenevinylene), indicating that CT -states of C 60 (at 4.5 eV) are involved in formation of a dipole at these interface as well. [9] The energy level alignment at interfaces of C 60 and F8 further supports this proposed model for organic-organic interfaces. As shown in Figure 3 the energy of the positive polaronic level of F8 falls at 5.2 eV, which is 0.7 eV higher than the energy of the CT -states of C 60 .…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Note that the same alignment of the C 60 energy levels has been observed at its interfaces with oligomer homologues of poly(para-phenylenevinylene), indicating that CT -states of C 60 (at 4.5 eV) are involved in formation of a dipole at these interface as well. [9] The energy level alignment at interfaces of C 60 and F8 further supports this proposed model for organic-organic interfaces. As shown in Figure 3 the energy of the positive polaronic level of F8 falls at 5.2 eV, which is 0.7 eV higher than the energy of the CT -states of C 60 .…”
supporting
confidence: 63%
“…The examples that have been reported show typically marginal vacuum level shifts, unless the interface is composed of a donor-acceptor pair of materials. [7][8][9] Concerning donor-acceptor interfaces, a generalized description of the energetics at such organic-organic interfaces with the IDIS model has been proposed. [10] The interactions at such interfaces ware assumed sufficiently strong to induce a density of interfacial states that is large enough to accommodate for significant charge exchange across the interface and, in result, the formation of an interfacial dipole layer.…”
mentioning
confidence: 99%
“…In another study, however, deviations from this pinning behavior have been found [105]. Thus, the individual energy level alignments between organic/metal interfaces are critical [72,[106][107][108][109][110][111][112]. Interfacial dipoles formed at the organic semiconductor/electrode interface change the effective metal work function and thus affect the V OC as well [72,108,109,113,114].…”
Section: Influence Of Electrical Contacts and Open Circuit Voltagementioning
confidence: 85%
“…First, it has been shown by photoelectron spectroscopy that a dipole of some 0.25 eV, pointing towards the PPV, is created at the interface between a film of PPV oligomers and C 60 . [57] Second, the higher polarizability of the PCBM (through the higher value of e) means that the cost of charging the molecule is less. Finally, the large density of states in the fullerene compared to the polymer [58,59] may create a significant entropic driving force.…”
Section: Mechanism For Hole-mobility Enhancementmentioning
confidence: 99%
“…[63,64] The formation of a CT state is consistent with the evidence for interface dipoles at PPV/fullerene interfaces. [57] Optical excitation of this band should result in weakly bound polaron pairs that may be easily separated to deliver electrons and holes to the respective materials. One tentative explanation for the observed hole-transport behavior in MDMO-PPV:PCBM blends is, therefore, that hole polarons generated in the MDMO-PPV phase may be transferred into the interfacial CT state, for which transition there is no energy barrier, and are then transported by hopping between the CT complexes.…”
Section: Mechanism For Hole-mobility Enhancementmentioning
confidence: 99%